Analysis of benefit: cost ratio in drip irrigation and fertigation in greater yam (Dioscorea alata) + maize (Zea mays) intercropping system (Current Horticulture, 2024)
A field experiment was conducted at Regional Centre, ICAR-Central Tuber Crops Research Institute, Bhubaneswar, Odisha, India, during 2015-16 and 2016-17 to study drip irrigation and fertigation in greater yam (Dioscorea alata L.) + maize (Zea mays L.) intercropping system. The treatments I2F4 and I2F3 resulted in 31.8 and 29.9% higher tuber equivalent yield, respectively than the control. Drip irrigation increased fertilizer responsiveness in greater yam + maize intercropping system. However, response to fertilizer was higher under partial deficit irrigation. Thus 20% more fertilizers can be recommended under drip fertigation than surface irrigation with soil application. Drip irrigation reduced cost on weeding and irrigation. The total cost reduction (excluding capital cost, harvesting and threshing) was about 8.3% (` 11,500/ha) and 7.1% (` 9,900/ha) due to drip irrigation at I1F2 and I2F2, respectively compared to surface flood irrigation at the same level of fertilizer application (control). The gross and net returns in treatment I1F2 were 5.2 and 3.1% higher, respectively than the control, saving 21.2% irrigation water. The treatment I3F2 resulted in 21.1 and 24.7% higher gross and net returns, respectively than the control. Thus, drip fertigation increased water- and fertilizer-use efficiency (20%).
Keywords: Tuber equivalent yield; Gross return; Net return; Intercropping; Fertigation; Drip irrigation